Pengembangan Instrumen Tes Berpikir Kritis Berbasis Pendekatan Socio Scientific Issues (SSI) pada Materi Virus: (Development of a Critical Thinking Test Instrument Based on the Socio-Scientific Issues (SSI) Approach on Virus Material) - Rahmatiya, Rahmatiya; Dama, Lilan; Usman, Nurul Fajryani; Retnowati, Yuliana; Mustaqimah, Nur (BIODIK, 2026)
This study aims to analyze the development of a critical thinking test instrument based on the Socio-Scientific Issue (SSI) approach. The abstract nature of virus material demands learning and evaluation that not only emphasizes memorization of concepts, but also connects the concept of viruses with real-life problems. Therefore, an innovative approach is needed to improve students' critical thinking skills with the Socio-Scientific Issue (SSI) approach. The test instruments used by teachers have not accommodated critical thinking skills or teachers still predominantly measure low cognitive abilities, namely C1 and C2. This study uses the Research and Development (R&D) research method along with the ADDIE development model. The population used was 88 grade XI students at MAN 2 Gorontalo Regency. The sample consisted of 35 students who participated in a limited-scale trial with a purposive sampling technique. The results of the research and development that have been carried out, the critical thinking test instrument based on the Socio-Scientific Issue (SSI) approach on virus material was declared "Very Valid" based on the results of the validity test by material experts and construct experts. This is demonstrated by the average validity score of 97% from subject matter experts and 98% from construct experts. The results of the item validity and reliability tests indicate that all items are valid and reliable. Furthermore, the test instrument was also declared "Very Practical," with an average practicality score of 98% from teachers and 86% from students. These results indicate that the test instrument is valid and suitable for use as an evaluation tool in the learning process. Abstrak.Penelitian ini bertujuan untuk mengembangkan instrumen tes berpikir kritis berbasis pendekatan Socio Scientific Issue (SSI). Instrumen tes yang digunakan oleh guru belum mengakomodasi kemampuan berpikir kritis atau guru masih dominan mengukur kemampuan kognitif rendah yaitu C1 dan C2. Penelitian ini menggunakan metode penelitian Research and Development (R&D) bersama dengan model pengembangan ADDIE. Populasi yang digunakan adalah 88 peserta didik kelas XI di MAN 2 Kabupaten Gorontalo. Sampel terdiri dari 35 peserta didik yang berpartisipasi dalam uji coba skala terbatas dengan teknik purposive sampling. Hasil penelitian dan pengembangan yang telah dilakukan, instrumen tes berpikir kritis berbasis pendekatan Socio Scientific Issue (SSI) pada materi virus dinyatakan “Sangat Valid” berdasarkan hasil uji validitas ahli materi dan ahli konstruk. Hal ini ditunjukkan oleh rata-rata skor validitas ahli materi sebesar 97% dan rata-rata skor validitas ahli konstruk sebesar 98%. Hasil uji validitas butir soal dan reliabilitas menunjukkan bahwa seluruh butir soal dinyatakan valid dan reliabel. Selanjutnya, instrumen tes juga dinyatakan “Sangat Praktis”, dengan skor kepraktisan rata-rata 98% dari guru dan 86% dari peserta didik. Hasil ini menunjukkan bahwa instrumen tes yang dibuat valid dan layak digunakan sebagai alat evaluasi pada proses pembelajaran.